Avaliação da política de incentivos fiscais no desenvolvimento econômico-social do Município de Aquiraz – Ceará - Pereira, Francisco Wellington Ávila (2008)
The programs developed to provide economic growth, job generation, income and social development embrace multiple government strategies. The Industry Development Fund, FDI/PROVIN, is a program used by the Government of Ceará to attract companies aiming at the generation of jobs and income into the region. There is a dilemma that can be seen between those who are against and those who are in favor of tax incentive, since there is public revenue resignation in behalf of the uncertainty of a future social economic reward. This study aimed to evaluate the main effects of the FDI in the social economic development of the city of Aquiraz. The economic and social contributions generated by the companies having had tax incentives in the period from 1997 to 2007 were evaluated through the wealth generated, number of jobs created, value of wages, evolution of the Goods and Service Circulation Tax (ICMS) quota distribution index, formation of the county Gross Domestic Product (PIB) and public revenue generation. It was carried out a collection of data in the State Treasury Bureau and in the County Finance and Budgetary Execution Bureau, as well as a Internet research. It is possible to conclude there was loss of income to the State Government and profit to the County, and jobs were generated in the city with average wages bigger than other economy sectors. However it is an onerous and located politics, which should be reviewed by the Federal Government, so that other mechanisms could be developed to promote a reduction on the country regional differences and a greater efficiency in resources